Notch1 regulates the initiation of metastasis and self-renewal of Group 3 medulloblastoma. Issue 1 (December 2018) - Kahn, Suzana; Wang, Xin; Nitta, Ryan; Gholamin, Sharareh; Theruvath, Johanna; Hutter, Gregor; Azad, Tej; Wadi, Lina; Bolin, Sara; Ramaswamy, Vijay; Esparza, Rogelio; Liu, Kun-Wei; et al.
Abstract Medulloblastoma is the most common malignant brain tumor of childhood. Group 3 medulloblastoma, the most aggressive molecular subtype, frequently disseminates through the leptomeningeal cerebral spinal fluid (CSF) spaces in the brain and spinal cord. The mechanism of dissemination through the CSF remains poorly understood, and the molecular pathways involved in medulloblastoma metastasis and self-renewal are largely unknown. Here we show that NOTCH1 signaling pathway regulates both the initiation of metastasis and the self-renewal of medulloblastoma. We identify a mechanism in which NOTCH1 activates BMI1 through the activation of TWIST1. NOTCH1 expression and activity are directly related to medulloblastoma metastasis and decreased survival rate of tumor-bearing mice. Finally, medulloblastoma-bearing mice intrathecally treated with anti-NRR1, a NOTCH1 blocking antibody, present lower frequency of spinal metastasis and higher survival rate. These findings identify NOTCH1 as a pivotal driver of Group 3 medulloblastoma metastasis and self-renewal, supporting the development of therapies targeting this pathway. Group 3 medulloblastoma is an aggressive pediatric brain tumour that disseminates through the leptomeningeal cerebral spinal fluid. Here, the authors show that in Group 3 medulloblastoma NOTCH1 activates BMI1 through the activation of TWIST1, driving metastasis and self-renewal, and in mouse models a NOTCH1 blocking antibody decreased spinal metastases.